Mucosal Immunity and B Cells in Teleosts: Effect of Vaccination and Stress - Parra, David; Reyes-Lopez, Felipe E.; Tort, Lluis (Frontiers in Immunology, 2015)
Fish are subjected to several insults from the environment, which may endanger animal survival. Mucosal surfaces are the first line of defense against those threats and they act as a physical barrier to protect the animal but also function as immunologically active tissues. Thus, four mucosal-associated lymphoid tissues have been described in fish, which lead the immune responses in gut, skin, gills and nose. Humoral and cellular immunity, as well as its regulation and the factors that influence the response in these mucosal lymphoid tissues is still not well known in most of fish species. Mucosal B-lymphocytes and immunoglobulins (Igs) are one of the key players in the immune response after vaccination. Recent findings about IgT in trout have delimited the compartmentalization of immune response in systemic and mucosal. The existence of IgT as a specialized mucosa Ig gives us the opportunity of measuring mucosal specific responses after vaccination, a fact that was not possible until recently in most of the fish species. Vaccination process is influenced by several factors, being stress one of the main stimuli determining the success of the vaccine. Thus, one of the major goals in a vaccination process is to avoid possible situations of stress, which might interfere with fish immune performance. However, the interaction between immune and neuroendocrine systems at mucosal tissues is still unknown. In this review we will summarized the latest findings about B-lymphocytes and immunoglobulins in mucosal immunity and the effect of stress and vaccines on B cell response at mucosal sites. It is important to point out that a small number of studies have been published regarding mucosal stress and very few about the influence of stress over mucosal B-lymphocytes.